An institutional analysis of bank regulation - Gleta, Jakub; Teplý, Petr (Univerzita Pardubice, 2012)
This article focuses on the institutional content and impact of the new Basel Capital Accord, commonly known as Basel III. These rules were enacted in response to the recent developments in global financial markets and to introduce some substantial changes into established regulatory approaches. We use the method of “process tracing” of the neo-proceduralist school to assess whether Basel III is a victim of regulatory capture or not. We find that Basel III met a number of procedural requirements and is not a victim of regulatory capture. On the other hand, we point to the fact that there remain numerous open issues that could undermine the as yet unfinished outcome and cause Basel III to join its predecessors in their fate.
Keywords: banking; basel II; basel III; institutions; neo-proceduralism; banking regulation